Influence of natural gas composition on adsorption in calcite Nanopores: A DFT study - Elkhansa Elbashier (14152815) (2021)
Density functional theory is used to study the adsorption of natural gas components in calcite (10.4) cylindrical nanopores with 1–4 nm diameters. The change of adsorption energy with the diameter of the nanopores is studied for CH4 and CO2 gases. The results of the simulation calculations showed that as the nanopore diameter decreases, the adsorption energy increases exponentially due to the geometry of the smallest pore that increases the affinity of the molecules to the surface. Compared to the flat surface, for both molecules, CH4 and CO2, the interaction energy of the molecule with the nanopore could increase to more than five times depending on pore radius and molecule type. Additionally, in all cases, CO2 has a greater affinity to the surface than CH4; thus, it is more affected by the surface curvature and energy. For methane, adsorption energy on the flat surface is-0.0025 eV/Å2, while on the smallest nanopore, it increases to-0.0139 eV/Å2. On the other hand, the adsorption energy of carbon dioxide has increased from-0.0046 eV/Å2 on the flat surface to-0.0263 eV/Å2 on the smallest nanopore. To estimate the nanopore saturation of the gas, the capacity of the gases’ adsorption was calculated. The nanopores absorbed up to 28 and 24 molecules of CH4 and CO2, respectively, and the adsorption energy decreased to −0.0062 and −0.0075 eV/Å2 for each. Although the nanopore was filled spatially by the molecules, its surface still has an affinity to absorb more gas molecules energetically. These findings could be useful for estimating the adsorbed gas on carbonate rocks. Other Information Published in: Applied Surface Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.apsusc.2021.150940